An Aplikasi Sistem Pakar Diagnosa Penyakit Mata Pada Manusia Menggunakan Metode Certainty Factor Berbasis Web - Wijaya, Bayu Angga; Tanjung, Juliansyah Putra (Sinkron : jurnal dan penelitian teknik informatika, 2020)
Eye is the important senses. If the eye is disrupted then ignore it, it will disturb. In fact, many people delay to checked eye diseases that them suffered, due to the lack of knowledge society, the cost is quite expensive and the imbalance between patients and doctors so that should be queued if will check the eye health. It is necessary for the expert system that can diagnose eye diseases, so a people can checking their eye diseases suffered without have to go to the doctors. This expert system is based on web with the programming language PHP and MySQL database. In the process of withdrawal conclusion, system using the certainty factors method that use a value to assume degree of confidence from an expert to a data. Expert system provides results in the form of the possibility of illness suffered, the value of the percentage of beliefs from the illness and the treatment solution based on the value of confidence that given and system is able to know the type of eye disease experienced by the user based on the symptoms chosen by the user. So, it can help the people to know the eye disease their suffered and the action can be done faster.